Love Scam di Selangor: Satu Penerokaan terhadap Modus Operandi Jenayah Siber ke atas Wanita Profesional - Alavi, Khadijah; Sooed, Mohammas Syahrul Azha; Bakar, Al-Azmi (UUM Press, 2018)
Love Scam is a cyber or commercial crime targeting women, especially professional women's who have lost millions of ringgit in Malaysia. This study explores the factor of victim involvement and modus operandi used by the scammer. The interviews were conducted at the District Police Headquarters (IPPD) in Selangor. A total of five love scam victims were interviewed, with the assistance of police officers dealing with commercial crime cases. The findings show that prominent factors identified are the perpetrators sweet talk, socializing, easy internet access and self pressure among victims. The modus operandi often used by the perpetrators to trap victims is through fraud profile picture in social media, fake sweet promises, and packaged delivery and posing as representatives of tax agencies.